Setting some morphological and physiological criteria for directing football players under the age of 17 to defense axial positions - Lourci , yazid; Ben mesbah, kamel (sports creativity, 2025)
The research aims to identify the most important morphological and physiological measurements for directing football players under the age of 17 years to the defense centers, and To confirm our study, we deliberately selected 30 players as a sample of research representing the middle of 10 clubs active at the level of the Algerian First Division (under 17 years of age) football for the 2018/2019 sports season.We used The descriptive method and we collected the data by using the physical measurements necessary and then statistical processing of the data ,The research has yielded the following results: the players levels of defense are related of the play positions in measuring height, weight, big, muscle mass index shows the levels are in favor of the average level and the weak level in terms of physiological standards